If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying A = p * m + p Multiply p * m A = mp + p Solving A = mp + p Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Simplifying A = mp + p
| 3y+8-y=2+y+10 | | 2z-9=3z-7 | | 24x^2y+12xy^2-12y=0 | | 6x+2x-15=25 | | 9-14=5 | | 6/6+4/6=4 | | 4n+5=28 | | 7(a-3)=3(5+a) | | -9x+6x=12x+15 | | 2a+3b-6=4c | | 2x^2+16x+14= | | 3+x/5=14 | | 9+2y=17 | | m=2m+6 | | 15x^2+40x-400=0 | | 9f-4=f+19 | | 222-544= | | 10=-16/r+8 | | 15/e-1=-46 | | 6x-8=7+3 | | 4/x=-32 | | -56/m=-2 | | 5=-25/x | | x/27-32=-4 | | j/-8-13=-35 | | 2-X*66=h | | -30=l/-5-24 | | k/6-16=4 | | 10=c/-4-2 | | 684/18=j/-21 | | 4v+12=48 | | -768/32=p/5 |